2022
DOI: 10.3390/nu14235078
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Food Security of UK Adults Aged 20–65 Years (COVID-19 Food Security and Dietary Assessment Study)

Abstract: The first UK lockdown greatly impacted the food security status of UK adults. This study set out to establish if food procurement was adapted differently for different income groups and if this impacted dietary intakes disproportionately. Adults (n = 515) aged 20–65 years participated in an online survey with 56 completing a 3–4 day diet diary. Food availability was a significant factor in the experience of food insecurity. Similar proportions of food secure and food insecure adapted food spend during lockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Verificou-se que o diário alimentar é um método utilizado para a população em geral durante o cenário da pandemia da COVID-19 para rastreio de desejos alimentares, frequência e dificuldade de resistir a estes desejos, bem como estados emocionais relacionados aos desejos (DEVONPORT et al, 2022). O diário alimentar também já foi utilizado para verificar sinais de insegurança alimentar de uma amostra de indivíduos do Reino Unido (THOMAS et al, 2022).…”
Section: Avaliação Do Consumo Alimentarunclassified
“…Verificou-se que o diário alimentar é um método utilizado para a população em geral durante o cenário da pandemia da COVID-19 para rastreio de desejos alimentares, frequência e dificuldade de resistir a estes desejos, bem como estados emocionais relacionados aos desejos (DEVONPORT et al, 2022). O diário alimentar também já foi utilizado para verificar sinais de insegurança alimentar de uma amostra de indivíduos do Reino Unido (THOMAS et al, 2022).…”
Section: Avaliação Do Consumo Alimentarunclassified
“…For example, people who self-identi ed as isolating at this time were at higher risk of food insecurity over and above typical risk factors for food insecurity (1). Lockdowns also led to job losses and income reductions (1), also evidenced by the large increase in Universal Credit applications over the rst UK lockdown (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of limited food supplies, shielding restrictions and newly generated economic uncertainty, food insecurity may also have extended to more a uent groups, i.e., those who would not normally experience food insecurity. Indeed, one study found that the rst UK lockdown affected food access across all socioeconomic groups (4). In contrast, prior to the pandemic, research showed that food insecurity was concentrated among those in the lowest socio-economic groups (8, 9).…”
Section: Introductionmentioning
confidence: 99%